1996
DOI: 10.1021/ja9536025
|View full text |Cite
|
Sign up to set email alerts
|

Guanine Radical Cations Are Precursors of 7,8-Dihydro-8-oxo-2‘-deoxyguanosine But Are Not Precursors of Immediate Strand Breaks in DNA

Abstract: Biphotonic photoionization of frozen aqueous solutions of DNA at 248 nm has been shown by EPR spectroscopy to lead selectively to the guanine cation. In H 2 18 O under these conditions high levels of [ 18 O]-7,8dihydro-8-oxo-2′-deoxyguanosine are produced in a dose-dependent manner, confirming direct formation of this oxidation product by hydration of the guanine cation. Photoionization of defined oligonucleotides did not give rise to significant levels of immediate strand breaks but generated G-specific alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
197
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(221 citation statements)
references
References 33 publications
23
197
1
Order By: Relevance
“…Without MutY, irradiation of poly(dGC), [Ru (phen) 2 dppz] 2+ , and [Co(NH 3 ) 5 Cl] 2+ leads to an EPR signal with g = 2.004. This signal has been previously reported and is assigned to the guanine radical [67]. Irradiation of poly(dGC) in the presence of MutY, however, results in the appearance of new EPR signals with primary g values of 2.02 and 2.08 and a feature at 2.06.…”
Section: Redox Activation Of Muty By Guanine Radicalsupporting
confidence: 69%
“…Without MutY, irradiation of poly(dGC), [Ru (phen) 2 dppz] 2+ , and [Co(NH 3 ) 5 Cl] 2+ leads to an EPR signal with g = 2.004. This signal has been previously reported and is assigned to the guanine radical [67]. Irradiation of poly(dGC) in the presence of MutY, however, results in the appearance of new EPR signals with primary g values of 2.02 and 2.08 and a feature at 2.06.…”
Section: Redox Activation Of Muty By Guanine Radicalsupporting
confidence: 69%
“…3) as the trap on this basis. This modified base is often detected as a byproduct of oxidative damage (14,20,23,31,(33)(34)(35)(36). Although structural information is not available for PNA-containing duplexes, Williams and coworkers (37) recently determined the structure of a DNA duplex having an 8-OxoG substitution by x-ray crystallography and found that the oxidized base caused little perturbation.…”
Section: Resultsmentioning
confidence: 99%
“…Time-resolved spectroscopy reveals that the excited state of the quinone accepts an electron from a base in the DNA within 20 ps of excitation (21). The base radical cation (hole) can either recombine with the electron, be trapped by reaction with water and͞or oxygen, or migrate along the DNA helix to the lowest oxidation potential sites that serve as traps (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guanine bases (E 7 (G(−H) • , H + / G) = +1.29 V, Steenken and Jovanovic 1997) are the most easily oxidized sites in DNA (Colson et al 1992), but the methylperoxyl radical is able to oxidize them only to a minor extent (Milligan et al 1996). Since oxidation products of guanine bases do not produce SSBs under the conditions we have used here (Cullis et al 1996), this reaction may be safely ignored. Redox active amino acids present in the histone proteins of the SV40 minichromosome such as tyrosine (E 7 = +0.93 V, Harriman 1987;DeFilippis et al 1989) and tryptophan (E 7 = +1.03 V, Harriman 1987; Wardman 1989) may be oxidized more extensively by the methylperoxyl radical.…”
Section: Discussionmentioning
confidence: 98%